Colonização de orofaringe como fator de risco para pneumonia associada à ventilação por Staphylococcus aureus, uso de antimicrobianos, multirresistência e prognóstico de pacientes em unidade de terapia intensiva de adultos - Moreira, Michel Rodrigues (2013)
The colonization of the oropharynx plays an important role in the pathogenesis of ventilator-associated pneumonia (VAP). The presence of multidrug-resistant (MDR) microorganisms and inappropriate empirical antimicrobial therapy negatively affects the evolution of this infection. This study evaluated the involvement of ORSA and OSSA phenotypes in the etiology of VAPs, the importance of previous colonization of the oropharyngeal mucosa in the pathogenesis, the influence of the use of antibiotics in the emergence of MDR samples, and prognosis of patients when empirical antimicrobial therapy was introduced. We conducted a longitudinal, prospective study with the search for cases of oropharygeal colonization and VAP by S. aureus form May 2009 to August 2010. Additionally, two case-control studies were also performed; the first to assess the risk factors associated with colonization by S. aureus resistant to oxacillin (ORSA), with cases represented by colonized patients by ORSA and controls those colonized by S. aureus sensitive to oxacillin (OSSA), and the second study to evaluate factors associated with the development of VAP by MDR microorganisms, with cases represented by patients with VAP by bacteria MDR and controls those with VAP by bacteria non-MDR. In total, 346 patients were submitted to mechanical ventilation, of which 36.4% were colonized in the oropharynx with S. aureus, corresponding to 63.5% and 36.5% of ORSA and OSSA, respectively and risk of pneumonia was significant for both phenotypes. The high density of use of glycopeptides (269.56 DDDs / 1,000 patient-days) was related to colonization by ORSA (Pearson r = 0.57 / P = 0.02), and age > 60, previous antibiotic therapy and previous use of carbapenems were independent risk factors for the presence of this bacteria in the mucosa of the oropharynx. The VAP rate was 25.3% with MDR microorganisms representing nearly half (47.3%). The risk factors for this latter group were: length of hospital stay, use of corticoids and prior use of antibiotics. Empirical antimicrobial therapy was inappropriate in 30.9% of patients with VAP and was significantly associated with 30- day ICU mortality, as well as the etiology by microorganisms MDR. In summary, there was a significant relationship between the colonization of the oropharyngeal mucosa and the risk of VAP by both phenotypes. The ORSA colonization was associated with age> 60 years and previous exposure to antibiotics, the latter also associated with VAP by microorganisms MDR, which had a worse prognosis, as well as those who received inappropriate empirical antimicrobial therapy. The importance of VAPs in ICUs of hospitals in developing countries with limited resources in healthcare hospital is clear, making it necessary more and better epidemiological studies, and research on strategies easier and less costly in its prevention.